Framing and Gender in Voluntary Disclosure an Experimental Study - Siti Isnaniati; Eko Ganis Sukoharsono; Roekhudin; Rosidi (Cogent Business & Management, 2024)
This research aims to gain knowledge regarding the impact of positive or negative framing on decision-making according to gender, whether feminine or masculine, in voluntary disclosure. I was using an experimental study with a two-by-two factorial design. One of the factors is framing which is divided into 2 levels, namely positive framing and negative framing. This research hypothesis uses Two Ways Anova. This research shows that positive and negative framing has no effect on tax decisions regarding voluntary disclosure. Apart from that, masculine and feminine gender does not affect tax compliance for voluntary disclosure.
Keywords: 650; Framing; gender; voluntary disclosure